2010
DOI: 10.1021/ac100042e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nano-Optodes for Glucose Detection

Abstract: We have designed fluorescent nanosensors based on ion-selective optodes capable of detecting small molecules. By localizing the sensor components in a hydrophobic core, these nanosensors are able to monitor dynamic changes in concentration of the model analyte, glucose. The nanosensors demonstrated this response in vitro and also when injected subcutaneously into mice. The response of the nanosensors tracked changes in blood glucose levels in vivo that were comparable to measurements taken using a glucometer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 29 publications
0
88
0
Order By: Relevance
“…Various methods are available for concentration measurements through the use of enzymatic 1 , chemical 2 , or binding assays 3 . An interesting option is the use of fluorescent, protein-based in vivo biological sensors as reporters of the intracellular concentration of key metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are available for concentration measurements through the use of enzymatic 1 , chemical 2 , or binding assays 3 . An interesting option is the use of fluorescent, protein-based in vivo biological sensors as reporters of the intracellular concentration of key metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Our group utilizes a similar competitive binding scheme as the basis for functional nanosensors, but the sensing components are embedded in a lipophilic, highly plasticized polymeric particle into which glucose is extracted. 10,11 The hydrophobic particle design has several advantages that include isolation of the sensing components from biological fluid to prevent biofouling 12 and tunability of the system to adjust the dynamic range. 13 Our glucose-sensitive nanosensors successfully tracked changes in glucose levels when injected subcutaneously along the backs of mice.…”
Section: Introductionmentioning
confidence: 99%
“…13 Our glucose-sensitive nanosensors successfully tracked changes in glucose levels when injected subcutaneously along the backs of mice. 10 However, the monitoring time was limited to 1 h because of the loss of signal intensity at the injection site. Studies conducted by Gopee and coauthors 14 with intradermally injected quantum dots found that quantum dots migrated from the site of injection, with 60% of quantum dots remaining at the injection site after 24 h. Our nanosensors were implanted similarly in the skin, and migration was assumed to be the main cause of signal loss over time.…”
Section: Introductionmentioning
confidence: 99%
“…They would benefit from the fact that signal generation is based on a binding equilibrium (that means without consuming glucose) and is not sensitive to oxygen and other electrode-active interferences. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] Also, the fluorescence signal is available immediately after system turn-on during operation, while the electroenzymatic sensors require a certain warm-up time until stable signal levels are reached.…”
Section: Introductionmentioning
confidence: 99%